2015
DOI: 10.1007/s11627-015-9703-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient genetic transformation of Jatropha curcas L. by means of vacuum infiltration combined with filter-paper wicks

Abstract: Jatropha curcas L. (Jatropha) is a promising plant for the production of biodiesel in arid regions. To improve its productivity, it is important to understand the molecular functions of key genes in Jatropha, and to seek ways to modify important agronomic traits of Jatropha via molecular breeding. However, Jatropha is notorious for its recalcitrance to transformation. Thus, an improved protocol for efficient and reproducible Agrobacterium tumefaciens-mediated transformation is essential for molecular biology r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The results showed that BA and IBA affected the shoot with 0.5 mgL -1 TDZ, and the combination of 1.5 mgL -1 BA and 0.05 mgL -1 IBA was the most effective in regenerating shoots from calli (3.82 ± 0.18 shoots/explant) (Table 1 and Figure 1c, d). This finding was similar to previous results reported by Chiangmai et al (2015), Nanasato et al (2015) and Fufa et al (2019). The study was divergent from previous study in our lab by Khemkladngoen et al (2011) which showed that the combination of 3 mgL -1 BA and 0.1 mgL -1 IBA produced the highest regeneration frequency from calli due to genotype difference.…”
Section: Shoot Induction and Multiplicationsupporting
confidence: 93%
“…The results showed that BA and IBA affected the shoot with 0.5 mgL -1 TDZ, and the combination of 1.5 mgL -1 BA and 0.05 mgL -1 IBA was the most effective in regenerating shoots from calli (3.82 ± 0.18 shoots/explant) (Table 1 and Figure 1c, d). This finding was similar to previous results reported by Chiangmai et al (2015), Nanasato et al (2015) and Fufa et al (2019). The study was divergent from previous study in our lab by Khemkladngoen et al (2011) which showed that the combination of 3 mgL -1 BA and 0.1 mgL -1 IBA produced the highest regeneration frequency from calli due to genotype difference.…”
Section: Shoot Induction and Multiplicationsupporting
confidence: 93%
“…Seeds of Jatropha ( Jatropha curcas L.) variety IP-3P obtained from The Plantation Research and Development Center (Pakuwon), Ministry of Agriculture, Indonesia were used in this study 45 . Jatropha seeds were planted in a calcined granular diatomaceous earth (Isolite CG No.…”
Section: Methodsmentioning
confidence: 99%
“…To date, plant regeneration protocols have been developed using various types of explants (Wei et al, 2004;Jha et al, 2007;Deore and Johnson, 2008;Sharma et al, 2011;Toppo et al, 2012;Franco et al, 2014). Based on these regeneration systems, stable transformation procedures have been developed employing both Agrobacterium tumefaciens (Li et al, 2008;Kumar et al, 2011;Pan et al, 2010;Misra et al, 2012;Fu et al, 2015;Nanasato et al, 2015) or particle bombardment (Joshi et al, 2011;Purkayastha et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2008) first reported J. curcas genetic transformation via A. tumefaciens infection of cotyledon disc using the phosphinothricin herbicide as selective agent, however, the transformation efficiency was low (13%). Recently, Nanasato et al (2015) improved the rate of cotyledon transformation efficiency to 23.3% using vacuum infiltration for the step of bacterial inoculation and co-culture on filter-paper wicks instead of agar for the step of latency before shoot regeneration. Fu et al (2015) further increased the rate of transformation efficiency to 56% by optimizing kanamycin concentration in the selective medium and the duration of the selection process.…”
Section: Introductionmentioning
confidence: 99%